The lncRNA XIST regulates the tumorigenicity of renal cell carcinoma cells via the miR-302c/SDC1 axis - Zhang, Jianglei (Int J Clin Exp Pathol, 2017)
Long non-coding RNAs (LncRNAs) are thought to be involved in several biological processes in carcinomas. The aim of this study is to evaluate the roles of lncRNA-XIST in the tumorigenicity of renal cell carcinoma (RCC) cells via the miR-302c/SDC1 axis. In this study, the expression levels of miR-302c and XIST in RCC tissues and cells were analyzed by qRT-PCR. Cell proliferation was measured using MTT and colony formation assays, and cell apoptosis was detected using flow cytometry. The interaction between XIST and miR-302c was analyzed using a luciferase reporter gene assay. RCC tissues and cells exhibited decreased miR-302c expression and increased lncRNA-XIST expression. Furthermore, XIST negatively regulated miR-302c by directly binding regulatory sites in RCC cells. In addition, XIST silencing with siRNAs significantly inhibited the proliferation and promoted the apoptosis of 786-O and Caki-1 cells. Knockdown of Syndecan-1 (SDC1), a miR-302c target gene, yielded similar results as XIST silencing. In summary, XIST regulated the development and progression of RCC by inhibiting the miR302c/SDC1 axis.